Analysis of Using Song in English Vocabulary Mastery to Young Learners - Delvi Nanda Marpaung; Nursayani Maru’ao; Hidayati Daeli; Riswan Zega (Civiliza Publishing, Indonesia., 2025)
This research explores the use of song as pedagogical media in vocabulary mastery among young learners. Recognizing the important role of vocabulary in language mastery, this research aims to address the challenges faced by young learners in mastering English vocabulary, especially in a monotonous learning environment. The research focuses on two main aspects: the use of song in vocabulary mastery and teachers' perceptions of this method. Through qualitative research methods, including observations and interviews with English teachers, this research sought to analyze how song can facilitate vocabulary retention and engagement in young learners. This research used the data analysis technique by Miles and Huberman (1984), there were three stages in data analysis: data reduction, data display, and conclusion. The research findings show that song not only make learning fun, but also serve as an effective medium to improve vocabulary mastery. The research highlights the importance of selecting age-appropriate song that match students' interests and the importance of integrating song into the core teaching process rather than using them only as ice-breakers. The research concludes with recommendations for teachers to regularly incorporate song into their lesson plans and suggests future research to further explore the impact of different music genres on language learning. Overall, this research underscores the potential of music as a dynamic tool in fostering a positive learning environment and improving vocabulary mastery among young learners.